Solved by lagrange method
y^2 p^2+x^2q^2=x^2y^2z^2
"F(x,y,z,p,q)=y^2p^2+x^2q^2-x^2y^2z^2=0"
"\\frac{dx}{F_p}=\\frac{dy}{F_q}=\\frac{dz}{pF_p+qF_q}=-\\frac{dp}{F_x+pF_z}=-\\frac{dq}{F_y+qF_z}"
"\\frac{dx}{2py^2}=\\frac{dy}{2qx^2}=\\frac{dz}{2p^2y^2+2q^2x^2}=-\\frac{dp}{2xq^2-2xy^2z^2-2pzx^2y^2}=-\\frac{dq}{2yp^2-2yx^2z^2-2qzx^2y^2}"
"\\frac{pdx+qdy-dz}{2p^2y^2+2q^2x^2-2p^2y^2-2q^2x^2}=\\frac{pdx+qdy-dz}{0}=-\\frac{dp}{2xq^2-2xy^2z^2-2pzx^2y^2}=-\\frac{dq}{2yp^2-2yx^2z^2-2qzx^2y^2}"
"\\frac{dx}{2py^2}=\\frac{dy}{2qx^2}=\\frac{pdx+qdy-dz}{0}"
"p=0, q\\neq0"
Substitute this result into the initial equation, and we get:
Then:
"x^2q^2=x^2y^2z^2"
"q=yz"
"\\frac{y^2}{2}=lnz+c_1"
"p\\neq0, q=0"
Then:
"p=xz"
"\\frac{x^2}{2}=lnz+c_2"
The general solution:
"F(c_1,c_2)=F(\\frac{y^2}{2}-lnz, \\frac{x^2}{2}-lnz)"
Comments
Dear ANIK KUMAR GHOSH, thank you for leaving a feedback. We would be grateful if you describe these lines in more detail and give more comments.
This solution cant match my ans,, here some of line i can't understand.
Leave a comment